2019
DOI: 10.1101/707695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of adopted and non-adopted individuals reveals gene-environment interplay for education in the UK Biobank

Abstract: Individual-level polygenic scores can now explain ~10% of the variation in number of years of completed education. However, associations between polygenic scores and education capture not only genetic propensity but information about the environment that individuals are exposed to. This is because individuals passively inherit effects of parental genotypes, since their parents typically also provide the rearing environment. In other words, the strong correlation between offspring and parent genotypes results i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Simulations in an Icelandic dataset suggest that although GREML-KIN gives unbiased heritability estimates when family environmental influences are present, it over-estimates heritability if phenotypes are also substantially influenced by passive gene-environment correlation (Young et al 2018). The influence of passive gene-environment correlation for educational attainment in the UK Biobank is suggested by the lower SNP heritability for adoptees, whose rearing environments are less correlated with their genotypes (Cheesman et al, 2019). In the future, methods that can distinguish direct from indirect influences should be applied to neuroticism, education and other complex, socially-contingent traits (Eaves et al 2014;Visscher et al 2006;Young et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Simulations in an Icelandic dataset suggest that although GREML-KIN gives unbiased heritability estimates when family environmental influences are present, it over-estimates heritability if phenotypes are also substantially influenced by passive gene-environment correlation (Young et al 2018). The influence of passive gene-environment correlation for educational attainment in the UK Biobank is suggested by the lower SNP heritability for adoptees, whose rearing environments are less correlated with their genotypes (Cheesman et al, 2019). In the future, methods that can distinguish direct from indirect influences should be applied to neuroticism, education and other complex, socially-contingent traits (Eaves et al 2014;Visscher et al 2006;Young et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The findings are also consequential for genetic analyses more broadly. Some recent innovative analysis linking genetics to outcomes has taken seriously the confounding between children's genetics and family background when explaining children's later outcomes as adults, seeking to decompose PGS into direct (child) and indirect (parent) effects (26,31,32). This work has been motivated, in part, by previous research that used sibling comparisons in PGS to predict education.…”
Section: Discussionmentioning
confidence: 99%
“…The latter demonstrated that parental genotypes are associated with the environment they provide for the child (28,29). In fact, a growing body of evidence is showing the importance of considering gene-environment correlation when assessing polygenic effects on trait variation (30,31), especially for educationally relevant traits. Paralleling quantitative genetics results, a key point is that environmental measures are themselves heritable and GPS effects can be mediated by the environment, while environmental effects can be accounted for by genetics (genetic confounding).…”
Section: Introductionmentioning
confidence: 99%